Investigation on the influnce of collector height on the performance of solar chimney power plant - Al-Azawiey, S.S. (Asian Research Publishing Network, 2016)
The solar chimney power plant (SCPP) has the potential of converting solar energy indirectly to electrical energy using a combination of greenhouse technology, chimney technology, wind turbine and a generator. The present paper presents results of investigation on the performance of a prototype SCPP at different canopy height at constant chimney diameter and height of 0.32 m and 6.3 m, respectively. The investigation was conducted experimentally using an experimental model designed, fabricated, and subjected to measurements under Malaysia weather conditions. The experimental SCPP model has a collector diameter of 3 m and the absorbing medium was black painted pebbles while the transparent canopy was made of Perspex. The investigations were carried out for different canopy heights, above the absorber at the inlet section, of 0.05, 0.1, 0.15 and 0.2 m. The selected performance parameters for comparison were the air stream temperature in the collector, the mass flow rate created in the system measured at the chimney base, and the system efficiency during the day. The results have shown that the lowest canopy height, 0.05 m performed better than the other tested heights. It is recommended to extend the investigation by studying the system performance under various collector diameters. Â©2006-2016 Asian Research Publishing Network (ARPN).